New Zealand : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
The resilience displayed by the New Zealand economy throughout the turbulence is a clear testimony of the benefits of the economic reforms. Executive Directors appreciated these developments, and cautioned against reforms that could reduce labor and product market flexibility, and suggested that the authorities should be flexible and pragmatic in their implementation. They commended the authorities for the high quality of economic and financial statistics, and agreed that the country is well placed to absorb shocks without undue economic or financial distress.